Step
*
1
1
1
of Lemma
isOdd-sum
1. n : ℤ
2. 0 < n
3. f : ℕn ⟶ ℤ
4. Σ(f[x] | x < n) = (Σ(f[x] | x < n - 1) + f[n - 1]) ∈ ℤ
5. v : ℤ
6. Σ(f[x] | x < n - 1) = v ∈ ℤ
7. v1 : ℤ
8. f[n - 1] = v1 ∈ ℤ
9. v2 : ℕ
10. ||filter(λx.isOdd(f[x]);upto(n - 1))|| = v2 ∈ ℕ
11. ↑same-parity(v;v1)
12. ↑isEven(v)
13. ↑isEven(v1)
14. ↑isOdd(v2) supposing ↑isOdd(v)
15. ↑isOdd(v) supposing ↑isOdd(v2)
16. ¬↑same-parity(v2;||if isOdd(v1) then [n - 1] else [] fi ||)
⊢ ¬True
BY
{ (D -1 THEN AutoSplit) }
1
1. n : ℤ
2. 0 < n
3. f : ℕn ⟶ ℤ
4. Σ(f[x] | x < n) = (Σ(f[x] | x < n - 1) + f[n - 1]) ∈ ℤ
5. v : ℤ
6. Σ(f[x] | x < n - 1) = v ∈ ℤ
7. v1 : ℤ
8. f[n - 1] = v1 ∈ ℤ
9. v2 : ℕ
10. ||filter(λx.isOdd(f[x]);upto(n - 1))|| = v2 ∈ ℕ
11. ↑same-parity(v;v1)
12. ↑isEven(v)
13. ↑isEven(v1)
14. ↑isOdd(v2) supposing ↑isOdd(v)
15. ↑isOdd(v) supposing ↑isOdd(v2)
16. ↑isOdd(v1)
⊢ ↑same-parity(v2;1)
2
1. n : ℤ
2. 0 < n
3. f : ℕn ⟶ ℤ
4. Σ(f[x] | x < n) = (Σ(f[x] | x < n - 1) + f[n - 1]) ∈ ℤ
5. v : ℤ
6. Σ(f[x] | x < n - 1) = v ∈ ℤ
7. v1 : ℤ
8. ¬↑isOdd(v1)
9. f[n - 1] = v1 ∈ ℤ
10. v2 : ℕ
11. ||filter(λx.isOdd(f[x]);upto(n - 1))|| = v2 ∈ ℕ
12. ↑same-parity(v;v1)
13. ↑isEven(v)
14. ↑isEven(v1)
15. ↑isOdd(v2) supposing ↑isOdd(v)
16. ↑isOdd(v) supposing ↑isOdd(v2)
⊢ ↑same-parity(v2;0)
Latex:
Latex:
1.  n  :  \mBbbZ{}
2.  0  <  n
3.  f  :  \mBbbN{}n  {}\mrightarrow{}  \mBbbZ{}
4.  \mSigma{}(f[x]  |  x  <  n)  =  (\mSigma{}(f[x]  |  x  <  n  -  1)  +  f[n  -  1])
5.  v  :  \mBbbZ{}
6.  \mSigma{}(f[x]  |  x  <  n  -  1)  =  v
7.  v1  :  \mBbbZ{}
8.  f[n  -  1]  =  v1
9.  v2  :  \mBbbN{}
10.  ||filter(\mlambda{}x.isOdd(f[x]);upto(n  -  1))||  =  v2
11.  \muparrow{}same-parity(v;v1)
12.  \muparrow{}isEven(v)
13.  \muparrow{}isEven(v1)
14.  \muparrow{}isOdd(v2)  supposing  \muparrow{}isOdd(v)
15.  \muparrow{}isOdd(v)  supposing  \muparrow{}isOdd(v2)
16.  \mneg{}\muparrow{}same-parity(v2;||if  isOdd(v1)  then  [n  -  1]  else  []  fi  ||)
\mvdash{}  \mneg{}True
By
Latex:
(D  -1  THEN  AutoSplit)
Home
Index